Checklist of Poduromorpha (Collembola: Hexapoda) from Rio de Janeiro, Brazil - Da Silveira, Tatiana Cristina; de Mendonça, Maria Cleide (Zootaxa, 2019)
Poduromorpha order currently includes 11 families, 330 genera, and approximately 3.400 species, which are widely distributed. In Brazil, there are seven families, 48 genera, and 141 species, 74 of which occur in Rio de Janeiro State. Poduromorpha fauna has been investigated over the last years, especially those from the Brazilian southeastern region. The objective of the present work was to gather and expand information on Poduromorpha in Rio de Janeiro State from literature, data from Scientific Collections, dissertations, theses, and congress communications. As a result, 40 genera and 81 species have been recorded, five of which having been registered for the first time in Rio de Janeiro State.